2021
DOI: 10.1063/5.0050102
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic origin of compositional pulling effect in wurtzite (B, Al, In)xGa1−xN: A first-principles study

Abstract: Some fluctuations in composition are commonly observed in epitaxial-grown III-V multinary alloys. These fluctuations are attributed to compositional pulling effects, and an insight into their atomistic origin is necessary to improve current epitaxial growth techniques. In addition, the crystallinity of III-V multinary alloys varies widely depending on the constituent atoms. Using first-principles calculations, we then investigated different geometric configurations of gallium nitride (GaN)-based ternary alloy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…That is, the composition of the film is close to GaN near the InGaN/GaN interface, and the In content increases with the growth of InGaN, which is called the composition-pulling effect. This phenomenon has been intensively reported in experimental studies and is demonstrated to directly affect the quality of InGaN films. Several pseudosubstrate techniques are proposed to improve the quality of the InGaN film due to the composition-pulling effect Figure also shows that the formation energies of In Ga in all GaN layers are a monotonically decreasing function of strain from −5% (compressive) to 5% (tensile).…”
Section: Resultsmentioning
confidence: 94%
“…That is, the composition of the film is close to GaN near the InGaN/GaN interface, and the In content increases with the growth of InGaN, which is called the composition-pulling effect. This phenomenon has been intensively reported in experimental studies and is demonstrated to directly affect the quality of InGaN films. Several pseudosubstrate techniques are proposed to improve the quality of the InGaN film due to the composition-pulling effect Figure also shows that the formation energies of In Ga in all GaN layers are a monotonically decreasing function of strain from −5% (compressive) to 5% (tensile).…”
Section: Resultsmentioning
confidence: 94%
“…In addition we can also see that due to this stacking configuration, the Al and Ga atoms allow ordered alignments along the c-direction similar to the case of AlGaN in previous works. 42,43) The relatively higher formation energy of segregated Al 2 O 3 -Ga 2 O 3 layers can be associated to the strain between the Al 2 O 3 -Ga 2 O 3, brought about by the lattice mismatch of the pure phases. This strain can be lowered by having more distributed Al atoms as shown by the structure of the lowest energy configuration.…”
Section: Formation Of α-(Almentioning
confidence: 99%
“…In our FPCs [28], density functional theory (DFT)-based total energy calculations were implemented [42]. Vienna ab initio Simulation Package was used to perform the total energy calculations [43,44] using projector augmented wave formalism and a plane wave basis set, with a cutoff energy of 700 eV [45,46].…”
Section: Mathematical Approachmentioning
confidence: 99%
“…The metastability of AlGaN is associated with the atomic ordering as observed by x-ray diffraction (XRD) and selected area electron beam diffraction (SAED) [15][16][17][18][19][20][21][22][23][24][25]. On the other hand, theoretical investigations have predicted the ordered configurations of AlGaN [12,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%